2009
DOI: 10.3844/ajas.2009.882.887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Dexmedetomidine versus Fentanyl to Intrathecal Bupivacaine on Spinal Block Characteristics in Gynecological Procedures: A Double Blind Controlled Study

Abstract: Problem statement: The purpose of this study was to evaluate the onset and duration of sensory and motor block as well as operative analgesia and adverse effects of Dex Metedo Midine (DXM) or fentanyl given intrathecally with plain 0.5% bupivacaine for spinal anesthesia. Approach: seventy six patients classified as American Society of Anesthesiologists (ASA) status I, II and III scheduled for vaginal hysterectomy, vaginal wall repair and tension free vaginal tape were prospectively studied. Patients were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 19 publications
11
66
1
Order By: Relevance
“…They produce analgesia by the depressing release of C-fi ber transmitters and by hyperpolarization of post-synaptic dorsal horn neurons. 4,5,11 The complementary action of local anesthetics and alpha2 adrenoreceptor agonist accounts for their profound analgesic properties. The prolongation of motor block of spinal anesthetics may be the result of binding of alpha2 adrenoreceptor agonists to the motor neurons in the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They produce analgesia by the depressing release of C-fi ber transmitters and by hyperpolarization of post-synaptic dorsal horn neurons. 4,5,11 The complementary action of local anesthetics and alpha2 adrenoreceptor agonist accounts for their profound analgesic properties. The prolongation of motor block of spinal anesthetics may be the result of binding of alpha2 adrenoreceptor agonists to the motor neurons in the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Where gradually evolving studies can build the evidence for its safe use in central neuraxial blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the mechanism of this effect is not clear, it is proposed to act by binding to presynaptic C fibres, thus depressing the release of neurotransmitters, and by hyperpolarisation of postsynaptic dorsal horn neurons. 9,10 It is also shown to reduce the incidence of shivering in the postoperative period and the post-anaesthetic analgesic requirement. Similarly, studies have been done to determine the optimal intrathecal dose of dexmeditomidine.…”
Section: -11mentioning
confidence: 99%
“…Many studies [8][9][10] have shown that dexmeditomidine, when used as an intrathecal adjuvant, decreases postoperative analgesic requirement. This analgesic sparing effect was more pronounced in group S as compared with group P as requirement for rescue analgesic was significantly less in group S during the first six hours postoperatively.…”
Section: -11mentioning
confidence: 99%